Republic of Serbia : First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses Serbia's First Review Under the Stand-By Arrangement. The program is broadly on track. All end-March 2015 performance criteria and indicative targets were met with comfortable margins. All end-March structural benchmarks were implemented, although with a delay, and all prior actions were met. The economy has stabilized, on the back of lower oil prices and stronger than expected trading partner growth. Inflationary pressures remain subdued. The external position has strengthened. Despite monetary easing, credit growth remains sluggish, and nonperforming loans continue to pose a challenge. Risks to the program come from possible spillovers from regional developments and increase in market volatility, as well as delayed implementation of structural reforms.